Contribution of herpesviruses in the progression of periodontal and peri‐implant diseases in systemically healthy individuals. (19th July 2018) - Binshabaib, Munerah; ALHarthi, Shatha Subhi; Salehpoor, Danial; Michelogiannakis, Dimitrios; Javed, Fawad
Summary: The aim of this review was to assess the contribution of herpesviruses in the subgingival oral biofilm in the progression of periodontal and peri‐implant diseases in systemically healthy individuals. The literature review was customized to summarize the pertinent information for the following reasons: (1) A systematic review regarding the role of herpesviruses in the etiopathogenesis of periodontal disease has recently been published; and (2) a limited number of studies have assessed the association of herpesviruses with peri‐implant diseases. To date, five observational studies have assessed the presence of herpesviruses in the subgingival oral biofilm of individuals with peri‐implant diseases. In these studies, dental implants were in place for up to approximately 8 years. In two studies, human cytomegalovirus (HCMV) was more often isolated from the peri‐implant sulci of sites with than without peri‐implantitis. In one study, a low prevalence of HCMV compared with Epstein‐Barr virus (EBV) was associated with the progression of peri‐implantitis. In previous studies, the presence of EBV in the subgingival oral biofilm was associated with the onset of peri‐implantitis and peri‐implant mucositis, respectively. Major limitations of the studies assessed were the absence of blinding and lack of power analysis for sample size estimation. In conclusion, the presence of herpesviruses in the periodontal and peri‐implant subgingival oral biofilm is an indicator of periodontal and peri‐implant diseases in systemically healthy individuals; however, further studies with a statistically justified sample‐size are needed to understand and refine this association.